2017
DOI: 10.24036/jh.v15i2.6564
|View full text |Cite
|
Sign up to set email alerts
|

THE IMPACT OF TRANSLATION TECHNIQUES TOWARD THE QUALITY OF TRANSLATION: A Case Study on a Social Text

Abstract: Quality of translation is one of the most important aspect in translation studies. This article aims at reporting the impact of translation techniques toward the quality of translation in term of accuracy, acceptability, and readibility. This descriptive qualitative research focused on single case. Objective data were taken from the "Asalusul Elite Minangkabau Modern: Respons terhadap Kolonial Belanda Abad XIX/XX" and its source text "The Minangkabau Respons to Dutch Colonial Rule in the Nineteenth Century". T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 5 publications
2
5
0
2
Order By: Relevance
“…This study shows similar result with (Ardi, 2016) who found that the translation quality in a text in this case is social text or non fiction text is quite good in the term of accuracy, acceptability, and readability, though compared to this study it had slight difference in which the translation quality assessment was rated in the term of accuracy, clarity, and reability. Moreover, the present study was conducted on a non fiction text that does not require highly accurate translation but highly readable translation.…”
Section: Unreadable or Not Readable Classificationsupporting
confidence: 87%
“…This study shows similar result with (Ardi, 2016) who found that the translation quality in a text in this case is social text or non fiction text is quite good in the term of accuracy, acceptability, and readability, though compared to this study it had slight difference in which the translation quality assessment was rated in the term of accuracy, clarity, and reability. Moreover, the present study was conducted on a non fiction text that does not require highly accurate translation but highly readable translation.…”
Section: Unreadable or Not Readable Classificationsupporting
confidence: 87%
“…Based on the finding it is also clearly found that literary work represents natural communication by shifting in the translation product. It is in line with the statement of Tianmin (2006) that translating literary works especially novel is different from translating science that should keep the form to avoid the changing of the message or keep the form in TL (Ardi, 2016). In his research related to social science text, some shift is conducted to keep the message.…”
Section: Unit Shift From Clause To Wordsupporting
confidence: 66%
“…Hasil kajian ini sejalan dengan kajian-kajian tersebut karena pada hasil terjemahan Millie juga ditemukan teknik-teknik terjemahan yang meliputi adaptasi, amplifikasi, peminjaman, kalke, kompensasi, deskripsi, kreasi diskursif, kesepadanan lazim, generalisasi, amplifikasi linguistik, penerjemahan harfiah, modulasi, reduksi, substitusi, transposisi, partikularisasi, dan variasi. Beberapa temuan pada kajian ini juga sejalan dengan hasil kajian (Ardi, 2016) yang membahas kualitas hasil terjemahan buku sejarah berjudul The Minangkabau Respons to Dutch Colonial in Nineteeth Century ke dalam bahasa sasaran bahasa Indonesia. Berdasarkan kajiannya, dikemukakan beberapa teknik penerjemahan berikut penilaian kualitas terjemahan dari beberapa responden.…”
Section: Temuan Lainnyaunclassified